HISTOPATHOLOGICAL ANALYSIS OF INCISION WOUND HEALING IN RATS TREATED WITH PIG BLOOD-DERIVED PLATELET-RICH PLASMA GEL - Stevanny Lastra; I Wayan Wirata; Ni Luh Eka Setiasih; I Gusti Ngurah Sudisma; I Wayan Gorda; I Made Kardena (Buletin Veteriner Udayana, 2025)
Platelet Rich Plasma (PRP) can be used as a regenerative treatment to enhance the activity of growth factors in the blood with the aim of wound healing. PRP can enhance neovascularization, fibroblast formation, and tissue epithelialization more quickly and efficiently. This study aims to determine the histopathological observation of incision wound healing on the skin of white rats given PRP gel. This study used male white rats of the Wistar strain, aged 2-2.5 months and weighing 200-300 grams. The 27 rats used were divided into three treatment groups: P0 (negative control, given 0.9% NaCl solution), P1 (positive control, given Bioplacenton), and P2 (given PRP Gel). The treatment was administered once after the skin had been incised and was given only once. On days 1, 5, and 11, a biopsy of the skin organ was performed for histopathological examination. Histopathological examination includes four indicators: inflammatory cell infiltration, angiogenesis, fibroblasts, and collagen density. Data were analyzed using the Kruskal-Wallis test followed by the Mann-Whitney test, and then described descriptively. The research results show that the infiltration of inflammatory cells and collagen density indicate a difference (P≤0,05) in the group of receiving PRP gel compared to the negative and positive control groups. However, there was no difference in angiogenesis and fibroblasts (P>0.05). In the wound healing process, the histopathological picture of incisional wound healing in the skin of white rats (Rattus norvegicus) given pig blood PRP gel shows an increase and development. Therefore, further research can be conducted to create a more optimal PRP gel formulation, and histopathological examinations can be carried out over a longer observation period to obtain significant results.